Ferroelectric‐Like Behavior in TaN/High‐k/Si System Based on Amorphous Oxide. (29th July 2021) - Feng, Ze; Peng, Yue; Shen, Yang; Li, Zhiyun; Wang, Hu; Chen, Xiao; Wang, Yitong; Jing, Meiyi; Lu, Feng; Wang, Weihua; Cheng, Yahui; Cui, Yi; et al.
Abstract: Thin‐film ferroelectric of HfO2 ‐based has gained broad interest for non‐volatile memories. The traditional theory with respect to doped hafnium oxide is based on the polycrystalline structure of the Pcb21 non‐centrosymmetric orthorhombic phase. While amorphous oxides also show ferroelectricity, which cannot be explained by the traditional theory. Here, ferroelectric‐like behavior is observed in the amorphous oxide‐based TaN/high‐k/Si system. Through strategically modulating the atomic layer of deposition conditions of the high‐k oxides, the evolution from paraelectric to ferroelectric‐like behavior is seen in TaN/Al2 O3 /Si capacitors. The interface chemistry of these stacks is systematically studied via in situ angle‐resolved X‐ray photoelectron spectroscopy. A mechanism for the ferroelectric‐like behavior is proposed based on interface ions‐vacancies displacement. This work sheds light on physics in ferroelectric‐like thin film devices. Abstract : Amorphous materials can also show ferroelectricity. However, the mechanism of this behavior is still not clear. The evolution from paraelectric to ferroelectric‐like behavior is observed in the TaN/high‐k/Si system via strategically modulated atomic layer deposition conditions. Based on in situ angle‐resolved X‐ray photoelectron spectroscopy and electrical characterization, a mechanism for the ferroelectric‐like behavior is proposed based on interface ions‐vacancies displacement.